A consensus protocol for unmanned aerial vehicle networks in the presence of Byzantine faults. (April 2022) - Cheng, Chien-Fu; Srivastava, Gautam; Lin, Jerry Chun-Wei; Lin, Ying-Chen
Abstract: This paper discusses the fault-tolerant consensus problem in Unmanned Aerial Vehicle Networks (UAVNets). In recent years, the applications of UAVNets have become more and more popular. Related applications include aerial photography, geological and topographic surveys, disaster monitoring, military applications, and so on. Therefore, it is very important to build a highly reliable and fault-tolerant UAVNets. However, the network architecture of UAVNets is very different from previous network architectures. Because UAVs fly at a high speed, the topology also varies quickly. Hence, how to collect sufficient messages to reach a consensus on the network for UAVs is a challenge. In this paper, the characteristics of the distributed UAVNets will be explored first. Then, based on the characteristics of the UAVNets, a new fault-tolerant consensus protocol called the UAV Consensus Protocol (UCP) is proposed. The proposed UCP consists of two phases: the message exchanging phase and the consensus making phase. The proposed UCP can solve the consensus problem with ⌞( nO -1)/3⌟+1 rounds of message exchange in the presence of ⌞( nO -1- aO )/3⌟ Byzantine faulty UAVs and aO away UAVs, where nO is the number of AUVs in the UAVNet. Moreover, the correctness of the proposed UCP is also proved in this paper.